'Constellations of singularities': the rejection of representative democracy in Coney's Early Days (of a better nation). Issue 1 (2nd January 2016) - Tomlin, Liz
Abstract: This article reflects on two specific performances of Coney's Early Days ( of a better nation ) (2014); an interactive piece of theatre which invites its audience, in role as three fractious regions of a post-revolutionary nation, to make a series of decisions to avert the pending crisis and unify the country once more. Running out of money, medical supplies and food, and with inadequate security to protect their remaining sources of power, decisions need to be made quickly on how to act and it is down to the audience to build or reject institutional structures of governance through which such decisions might be made. In both performances I attended, such institutional structures were either rejected or abandoned, providing a lens through which to examine the widespread scepticism of political institutions and democratic forms of representational governance that currently pervades Europe. In this article, I will reflect on how my affective experience within Coney's theatrical framework illuminated, for me, certain limitations of the trend in current political and philosophical theories to turn away from the authority of representative democracy towards a vision of disparate and singular acts of resistance.